2019
DOI: 10.1136/bmjopen-2018-028512
|View full text |Cite
|
Sign up to set email alerts
|

Profile of trauma mortality and trauma care resources at rural emergency departments and urban trauma centres in Quebec: a population-based, retrospective cohort study

Abstract: ObjectivesAs Canada’s second largest province, the geography of Quebec poses unique challenges for trauma management. Our primary objective was to compare mortality rates between trauma patients treated at rural emergency departments (EDs) and urban trauma centres in Quebec. As a secondary objective, we compared the availability of trauma care resources and services between these two settings.DesignRetrospective cohort study.Setting26 rural EDs and 33 level 1 and 2 urban trauma centres in Quebec, Canada.Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…(22) This finding echoes previous reports that highlighted significant disparities in access to high-quality emergency care in Canadian rural communities. (23,24) In the same way it was done for trauma care across the country, Canadian decision-and policy-makers could use the ED-HSMR to trigger in-depth performance assessment to help identify opportunities for improving emergency care structures and processes to improve patient outcomes. As worrisome as they are, wait times henceforth do not appear to be the only important risk factor impacting outcomes of ED patients with emergency sensitive conditions.…”
Section: Discussionmentioning
confidence: 99%
“…(22) This finding echoes previous reports that highlighted significant disparities in access to high-quality emergency care in Canadian rural communities. (23,24) In the same way it was done for trauma care across the country, Canadian decision-and policy-makers could use the ED-HSMR to trigger in-depth performance assessment to help identify opportunities for improving emergency care structures and processes to improve patient outcomes. As worrisome as they are, wait times henceforth do not appear to be the only important risk factor impacting outcomes of ED patients with emergency sensitive conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent trauma study showed that mortality in rural settings was 3.4 times higher than in urban environments and that 50% of trauma deaths occurred in the pre-hospital setting. 11 Locating victims and preparing timely trauma response and transport is critical. Yet in rural and remote areas it can be difficult to locate victims and deliver the necessary medical equipment (defibrillators and blood products) in a timely manner.…”
Section: The Challengementioning
confidence: 99%
“…[7][8][9] Our studies have shown that Canadian patients treated in rural hospitals are 20% more likely to die from a stroke than patients treated in urban hospitals and that rural Quebec trauma patients had pre-hospital and ED mortality rates 3.4 times higher than their urban counterparts. 10,11 We have also previously undertaken a number of research projects aimed at integrating scientific knowledge about rural EDs with the experiential knowledge of various stakeholders. [12][13][14] Among them, the Rural Emergency Care 360 project aimed to engage rural community members, healthcare providers, managers and policymakers in identifying needs, and imagining and taking ownership of initiatives likely to improve care and services.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a multiple case study to explore challenges and solutions for improving rural EDsan appropriate design for considering multiple stakeholders' perspectives within their context [17]. The province of Quebec has 26 EDs that meet the definition of "rural" used in our previous work, which is based on the following criteria (1) located in cities with a population of less than 15,000 (2016 census data); (2) 24/7 physician coverage; (3) hospital with patient admission capability; and (4) located more than 50 min of ground transport from a level 1 or 2 trauma centre [18]. Of Québec's 26 rural EDs, the research team selected, by convenience, two contrasting cases: Baie-Saint-Paul Hospital and Archipel Hospital at Cap-aux-Meules in the Magdalen Islands (see Map 1).…”
Section: Design and Case Selectionmentioning
confidence: 99%